2021
DOI: 10.1080/17445647.2020.1866697
|View full text |Cite
|
Sign up to set email alerts
|

Examining spatio-temporal mobility patterns of bike-sharing systems: the case of BiciMAD (Madrid)

Abstract: Over the past decades, Bike-Sharing Systems have been implemented in hundreds of cities all around the world. During this time, numerous academic studies have been published with analyses from different perspectives. The aim of this study is to build upon this research by bringing together a spatial and a temporal analysis of the cycling flow of BiciMAD, the Madrid Bike-Sharing System. By combining over 21 million GPS records and various maps the study visually explores cycling mobility patterns across the cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 23 publications
2
9
0
1
Order By: Relevance
“…Our results shed light on the influence of intersecting identities on the trip schedules, spatial preferences and travel speed of bike-share users and e-scooter riders navigating through Barcelona streets. In terms of timing, we found that bike-share and e-scooter trips overlap with commuting trips, a pattern also observed in the micromobility schemes of other cities (Li et al, 2020;Talavera-Garcia et al, 2021). Our findings, however, show that these modes are also highly used during the afternoon, especially by women, which might indicate a link between micromobility trips and non-work-related trip purposes.…”
Section: Discussionsupporting
confidence: 44%
“…Our results shed light on the influence of intersecting identities on the trip schedules, spatial preferences and travel speed of bike-share users and e-scooter riders navigating through Barcelona streets. In terms of timing, we found that bike-share and e-scooter trips overlap with commuting trips, a pattern also observed in the micromobility schemes of other cities (Li et al, 2020;Talavera-Garcia et al, 2021). Our findings, however, show that these modes are also highly used during the afternoon, especially by women, which might indicate a link between micromobility trips and non-work-related trip purposes.…”
Section: Discussionsupporting
confidence: 44%
“…In recent years, there has been a revolution in the use of geolocation data [ 22 ] for different forms of transport, providing us with a better understanding of movements in cities [ 23 ]. In addition, these data from geolocated devices and sensors provide a valuable source of information for pandemic monitoring and control [ 24 ], allowing for the identification of spatial transmission [ 25 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…An important overarching issue is that one must of course recognize that subway and bus rides are not walking. The same is true of related analysis of taxi cab (Guo & Karimi, 2017 ; Castro et al, 2013 ) and bike share data-sets (Talavera-Garcia et al, 2021 ). Transit mobility is an accommodation to the problem of mass and collective transport of huge numbers of people; transit trips are therefore very different than customer journeys.…”
Section: Existing Data Correspondences Between Retail Customer Journe...mentioning
confidence: 89%